PERAN ORANG TUA DALAM PENDIDIKAN FORMAL ANAK (Studi di Desa Taar Kecamatan Dulla Selatan) - Yoap Yolis Lakawen (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
Regarding the role of parents in the formal education of the child, it can be known that there is a gap between the expectation and the fact that in the village Taar Dulla Selatan District is very concern. The fact is found, that with the work of different parents such as driver Oto, motorcycle taxi, rush building, fishermen, farmers, almost the need of children do not notice such as writing books for kids later in school, Children's uniforms have been prepared or not, controlling their children in their growth and development, parents rarely follow the parents ' meeting, and always give the trust for the elderly child or Om or aunt to join the meeting between Teachers and parents, mothers are also working as laundry in some houses so sometimes if it is tired, the mothers of the Suda forget to pay attention to their children about learning, they think the children are already bisah independent or not, already Dinner or not, what else has learned or not. Therefore, the purpose of this research is to develop a sense of parental responsibility for its duties and roles, and is expected to foster knowledge and broaden parents ' horizons.Arifin suggests that the task of parents who need to be pone is, mother role as: 1. Have biological and physical needs. 2. Caring and taking care of the family patiently, in a consistent manner. 3. Educate, regulate and control the child. 4. Be examples and examples for children. Dad has a role as: 1. Father as a breadwinner. 2. Father as a husband who is full of understanding and giving security. 3. Father participated in child education. 4. As a protector or a firmly wise personage, loving the family.The research method used is a qualitative research method, the results of the study showed that the role of parents in the formal education of children studying in Taar village, Dulla Selatan District, has not undergone any changes, as it is seen from Parents ' participation in seeing their roles in supporting the child's formal education.Keyword: Parental role, Formal education